Characterization of a prototype rapid kilovoltage x‐ray image guidance system designed for a ring shape radiation therapy unit - Cai, Bin; Laugeman, Eric; Mazur, Thomas R.; Park, Justin C.; Henke, Lauren E.; Kim, Hyun; Hugo, Geoffrey D.; Mutic, Sasa; Li, Hua (Medical physics (Lancaster), 2019)
Purpose This study aims to characterize the performance of a prototype rapid kilovoltage (kV) x‐ray image guidance system onboard the newly released Halcyon 2.0 linear accelerator (Varian Medical Systems, Palo Alto, CA) by use of conventional and innovatively designed testing procedures. Methods Basic imaging system performance tests and radiation dose measurements were performed for all eleven kV‐cone beam computed tomography (CBCT) imaging protocols available on a preclinical Halcyon 2.0 LINAC. Both conventional CBCT reconstruction using the Feldkamp–Davis–Kress (FDK) algorithm and a novel, advanced iterative reconstruction (iCBCT) available on this platform were evaluated. Standard image quality metrics, including slice thickness accuracy, high‐contrast resolution, low‐contrast resolution, regional uniformity and noise, and CT Hounsfield unit (HU) number accuracy and linearity were evaluated using a manufacturer‐supplied QUART phantom (GmbH, Zorneding, Germany) and an independent image quality phantom (Catphan 500, The Phantom Laboratory, New York, NY). Due to the simplified design of the QUART phantom, we developed surrogate and clinically feasible strategies for measuring slice thickness and high‐ and low‐contrast resolution. Imaging dose delivered by these eleven protocols was measured using a computed tomography dose index phantom and pencil chamber with commonly accepted methods and procedures. A subset of measurements were repeated on a conventional C‐arm LINAC (TrueBeam and Trilogy, Varian Medical System) for comparison. Clinical patient images of pelvic and abdominal regions are also presented for qualitative assessment as part of a feasibility study for clinical implementation. Results Image acquisition time was 17–42 s on the Halcyon system compared with 60 s on the C‐arm LINAC systems. The kV imager projection offset, imaging and treatment isocenter coincidence and the couch three‐dimensional match movement all achieved less than1 mm mechanical accuracy. All major image quality metrics were within either the national guideline or vendor‐recommended tolerances. The designed surrogate approach with the QUART phantom showed a range of 0.24–0.35 cycles/mm for spatial resolution, a contrast‐to‐noise ratio (CNR) of 2–20 for FDK reconstruction and a tolerance of 0.5 mm for slice thickness. Other metrics derived from the Catphan images obtained on the Halcyon and C‐arm LINACs showed comparable values for the FDK reconstruction. The iterative reconstruction tended to reduce noise, as evidenced by a higher CNR ratio. The fast scan pelvis protocols for Halcyon resulted in 50% lower dose compared to the standard scans, and the thorax fast protocol similarly delivered 10% lower dose than the standard thoracic scan. Preliminary patient images indicated that rapid kV CBCT with breath‐hold is feasible, with improved imaging quality compared to free‐breathing scans. Conclusion Independent and comprehensive characterization of the kV imaging guidance system on the Halcyon 2.0 system demonstrated acceptable image quality for clinical use. The imaging unit onboard the Halcyon meets vendor specifications and satisfies requirements for routine clinical use. The fast kV imaging system enables the potential for volumetric CBCT acquisition during a single breath‐hold and the iterative reconstruction tends to reduce the noise therefore has the potential to improve the CNR for normal size patient.